Valproic Acid Combined with Zoledronate Enhance γδ T Cell-Mediated Cytotoxicity against Osteosarcoma Cells via the Accumulation of Mevalonate Pathway Intermediates - Wang, Shengdong; Li, Hengyuan; Ye, Chenyi; Lin, Peng; Li, Binghao; Zhang, Wei; Sun, Lingling; Wang, Zhan; Xue, Deting; Teng, Wangsiyuan; Zhou, Xingzhi; Lin, Nong; et al. (Frontiers in Immunology, 2018)
The long term survival of osteosarcoma has remained unchanged in the last several decades. Immunotherapy is proved to be a promising therapeutic strategy against osteosarcoma, especially for those with metastasis. Our previous study explored the sensibilization of zoledronate (ZOL) in γδ T cell-mediated cytotoxicity against osteosarcoma, but we haven’t yet elucidated the specific mechanism. Besides, high concentration is required to achieve these effects, whereas plasma ZOL concentration declines rapidly in the circulation. Valproic acid (VPA), a histone deacetylase inhibitor (HDAC-I) commonly used as the antiepileptic drug, has attracted much attention due to its synergistic antitumor efficacy with chemotherapy or immunotherapy. Here, we demonstrated that VPA combined with ZOL revealed the synergistic effect in enhancing antitumor efficacy of γδ T cells against osteosarcoma cells. This enhancement was mainly TCR-mediated and largely dependent on granule exocytose pathway. Of note, our findings indicated that ZOL sensitized osteosarcoma cells to γδ T cells by increasing the accumulation of the mevalonate pathway intermediates, which could be facilitated by VPA. We also found that this combination had similar effects on primary osteosarcoma cells. All the results suggested that VPA combined with ZOL could reduce the dose required to achieve a significant anti-tumor effect of γδ T cells, promoting it to be a novel therapy against osteosarcoma.